1994
DOI: 10.1084/jem.180.3.959
|View full text |Cite
|
Sign up to set email alerts
|

Reduced thymic maturation but normal effector function of CD8+ T cells in CD8 beta gene-targeted mice.

Abstract: SummaryCD8 is a cell surface glycoprotein on major histocompatibility complex class I-restricted T cells. Thymocytes and most peripheral T cells express CD8 as heterodimers of CD8ot and CD8/3. The intestinal intraepithelial lymphocytes (IEL), which have been suggested to be generated extrathymically, express CD8 predominantly as homodimers of CD8ot. We have generated CD8/3 gene-targeted mice. CD8tx + T cell population in the thymus and in most peripheral lymphoid organs was reduced to 20-30% of that in wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 52 publications
(61 reference statements)
6
37
0
Order By: Relevance
“…However, the role of CD8␤ in mature T lymphocytes is unclear, since CD8␤ gene-targeted mice (lacking CD8␤) appear to have normal CD8 effector function (38). Recently, studies have demonstrated that CD8␤ is required for the recognition of peptide ligands (39), increases CD8 coreceptor function (40), and influences CD8␣-associated p56 lck kinase activity (41).…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of CD8␤ in mature T lymphocytes is unclear, since CD8␤ gene-targeted mice (lacking CD8␤) appear to have normal CD8 effector function (38). Recently, studies have demonstrated that CD8␤ is required for the recognition of peptide ligands (39), increases CD8 coreceptor function (40), and influences CD8␣-associated p56 lck kinase activity (41).…”
Section: Discussionmentioning
confidence: 99%
“…8 V␣24 + T cells represent a human homologue of V␣14 + T cells which differentiate extrathymically in mice. 9,10 CD8␣/␣ + T cells may also differentiate extrathymically in humans because CD8␣/␣ + T cells reside in intestinal mucosa in nude mice, [11][12][13] and a large number of CD8␣/␣ + T cells was identified in the human fetal intestine. 14 As little is known about the relative contribution of the three pathways to T cell regeneration after allogeneic BMT, we analyzed T cell regeneration using putative phenotypic markers of thymus-dependent pathway (CD4 + CD45RA + T cells) and thymus-independent pathways (V␥9 + V␦2 + T cells, V␣24 + T cells, CD8␣/␣ + T cells and CD28 − T cells) after allogeneic BMT in children.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether DAF regulates CD8 ϩ T cell immunity, we infected groups of WT and Daf-1 Ϫ/Ϫ mice with LCMV-Armstrong, a virus strain that causes acute infection and a strong CD8 ϩ T cell response in the mouse (15,18,19). On day 6, 7, or 8 postinfection, mice were sacrificed, and the percentage and total number of CD4 ϩ and CD8 ϩ T cells in their spleens were determined by FACS.…”
Section: Daf-1 ϫ/ϫ Mice Had Markedly Increased Total and Ag-specific mentioning
confidence: 99%